2019
DOI: 10.3390/s19224832
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Structural Vibration with High-Rate Precise Point Positioning: Case Study Results Based on 100 Hz Multi-GNSS Observables and Shake-Table Simulation

Abstract: This contribution presents and assesses the methodology aiming at the characterization of the structural vibrations with high-rate GNSS measurements. As commonly employed precise point positioning (PPP) based on ionosphere-free linear combination of undifferenced signals may not meet the high requirements in terms of displacement precision, a modified processing strategy has been proposed. The algorithms were implemented in the own-developed GNSS processing software and validated using the designed experiment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 43 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…However, it is numerically challenging to estimate the related coefficients. In practice, the simplified stochastic modeling which is elevation dependent and ignores the correlations between the undifferenced observations is easy to implement, has a small computation burden, and also can produce a good estimation of the coordinate and other parameters (Cetin et al 2019;Paziewski et al 2019). Hence, it is assumed that there are no correlations among the triplefrequency observables.…”
Section: Methods For Triple-frequency Ppp Processingmentioning
confidence: 99%
“…However, it is numerically challenging to estimate the related coefficients. In practice, the simplified stochastic modeling which is elevation dependent and ignores the correlations between the undifferenced observations is easy to implement, has a small computation burden, and also can produce a good estimation of the coordinate and other parameters (Cetin et al 2019;Paziewski et al 2019). Hence, it is assumed that there are no correlations among the triplefrequency observables.…”
Section: Methods For Triple-frequency Ppp Processingmentioning
confidence: 99%
“…Here, the observation noise and multipath error can be detected in the frequency domain and are used to define the frequency band of structure movements. Multipath effect may reach up to several centimetres, which adversely affects the kinematic position accuracy (Paziewski et al 2019). The instantaneous impact of multipath is typically merged with phase noise.…”
Section: Filtering the Obtained Gnss Positions Time Seriesmentioning
confidence: 99%
“…The longerterm multipath effects have relatively long periods (several minutes and more) and low frequency with respect to the frequency band of structure movements. This implies that multipath effect can be effectively mitigated with a high-pass, band-pass or band stop filtering to obtain high-accuracy displacements (Paziewski et al 2019, Kaloop et al 2019. In this study, an 11-order Chebyshev band-pass filter with appropriate parameters for each event was implemented.…”
Section: Filtering the Obtained Gnss Positions Time Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moschas and Stiros [25] used 100 Hz GNSS data (Javad Delta receiver) to study a stiff pedestrian bridge and then analyze the displacement noise characteristics [26]. Paziewski et al [27] showed that 100 Hz PPP (recorded by Topcon Net-G5 receiver) derived displacements with the help of a filter. In addition, the high-rate GNSS receivers (model: Javad Sigma-G3TAJ) have also successfully been applied in monitoring seismic responses [28,29].…”
Section: Introductionmentioning
confidence: 99%